2022
DOI: 10.3389/fgene.2022.867736
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Elements, Sequence Turnover and Cyto-Nuclear Gene Transfer in Gymnosperm Mitogenomes

Abstract: Among the three genomes in plant cells, the mitochondrial genome (mitogenome) is the least studied due to complex recombination and intergenomic transfer. In gymnosperms only ∼20 mitogenomes have been released thus far, which hinders a systematic investigation into the tempo and mode of mitochondrial DNA evolution in seed plants. Here, we report the complete mitogenome sequence of Platycladus orientalis (Cupressaceae). This mitogenome is assembled as two circular-mapping chromosomes with a size of ∼2.6 Mb and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…orientalis , Larix sibirica and Picea sitchensis (Bong.) Carrière, which were composed of 2, 9 and 13 segments, respectively [ 4 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…orientalis , Larix sibirica and Picea sitchensis (Bong.) Carrière, which were composed of 2, 9 and 13 segments, respectively [ 4 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, gymnosperms only make up a small portion of the published plant mitogenomes; the majority come from angiosperms. Only 33 gymnosperm mitogenomes (including draft mitogenomes) have been reported to date [ 4 , 8 13 ]. Previous research has demonstrated that the gymnosperm mitogenome has undergone substantial changes in genomic size, physical structure, and gene composition [ 4 , 8 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two alternative hypotheses can explain their origins: (1) they were originally ancient angiosperm mitochondrial DNA fragments independently inserted into the common ancestor’s mitogenomes of the two Asia Gnetum clades or (2) they were initially seed plant descendants but had been lost from all gymnosperms except Gnetum . The second hypothesis is unlikely because Gnetum mitogenomes have drastically elevated rates of nucleotide substitutions with frequent gene loss [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%